Capital Market Volatility and Global Energy Crisis: A VAR and VECM Analysis - Vidya Ramadhan Putra Pratama (PT. Anagata Sembagi Education, 2026)
The recent increase in global capital market volatility is closely associated with the escalation of the global energy crisis, characterized by surging energy prices, supply disruptions, and geopolitical tensions. This study aims to examine the impact of the global energy crisis on capital market volatility by distinguishing short-run dynamics and long-run relationships between the variables. A quantitative time series approach is employed using Vector Autoregression and Vector Error Correction Model. The data represent indicators of the global energy crisis and stock market volatility across periods before, during, and after the energy crisis. The stationarity tests indicate that all variables are integrated of order one, while the Johansen cointegration test confirms the existence of a long-run equilibrium relationship between energy markets and capital markets. The VECM estimation reveals that capital market volatility adjusts significantly to deviations from long-run equilibrium following energy-related shocks. The impulse response analysis shows that stock market volatility responds positively to energy shocks in the short run, although the effects gradually diminish over time. Furthermore, the variance decomposition results indicate that the contribution of energy shocks to capital market volatility increases in the medium term. Overall, the findings support the hypothesis that the global energy crisis is a key determinant of capital market volatility and acts as a persistent source of macroeconomic uncertainty in financial markets